2015
DOI: 10.1159/000440701
|View full text |Cite
|
Sign up to set email alerts
|

The Moreau Strain of Bacillus Calmette-Guerin (BCG) for High-Risk Non-Muscle Invasive Bladder Cancer: An Alternative during Worldwide BCG Shortage?

Abstract: Background: Bacillus Calmette-Guerin (BCG) is the standard of care for adjuvant intravesical instillation therapy for intermediate- and high-risk non-muscle invasive bladder cancer (NMIBC) after complete transurethral resection. Increasing evidence suggests that there are marked differences in outcomes according to BCG substrains. BCG-Moreau was recently introduced to the European market to cover the issue of BCG shortage, but there are little data regarding the oncologic efficacy. Methods: We retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…The fact that suboptimal courses of BCG instillations may result in higher recurrence rates should not be overlooked, and for the very highest risk cases, higher progression rates with subsequent increase in T1 high-grade tumor mortality rate were observed [3]. Hofbauer et al [17] showed that some rarely used BCG strains such as BCG-Moreau strain can replace commonly used strains and thus may contribute to solve that shortage. This potential alternative from Biomed Lublin (Lublin, Poland), BCG-Moreau, has recently been introduced in the European market.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that suboptimal courses of BCG instillations may result in higher recurrence rates should not be overlooked, and for the very highest risk cases, higher progression rates with subsequent increase in T1 high-grade tumor mortality rate were observed [3]. Hofbauer et al [17] showed that some rarely used BCG strains such as BCG-Moreau strain can replace commonly used strains and thus may contribute to solve that shortage. This potential alternative from Biomed Lublin (Lublin, Poland), BCG-Moreau, has recently been introduced in the European market.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological evaluation was carried out according to the TNM system of Union for International Cancer Control and to the 1973 World Health Organization grading classification [19]. Patients with NMIBC on re-TUR and those with no residual tumor received an induction 6 weeks course of intravesical BCG followed by standard maintenance scheme, which consisted of intravesical BCG -standard dose -every week for 3 weeks given at 3, 6, 12, 18, 24, 30, and 36 months from initiation of therapy [20]. Only 303 (29%) patients completed the treatment protocol as planned [21].…”
Section: Patient Selection and Data Collectionmentioning
confidence: 99%
“…As an example, Sanofi Pasteur, one of the major producers of BCG, the current vaccine for TB, experienced significant manufacturing problems during 2012 and 2014. As a result, distribution of this vaccine was seriously compromised in several countries ( 123 ). Indeed, approximately 16.5 million doses shortfall of BCG occurred at the end of 2015 was estimated, using mathematical models, to be associated with 7,433 excess of TB deaths worldwide ( 124 ).…”
Section: Vaccine Manufacture and Distribution: Status Of Academic Pumentioning
confidence: 99%